THE ISSUE OF PUBLIC TRANSPORT STOPS (Perner's Contacts, 2011)
The article summarizes statistical data from the Czech Republic about public line transport and stops designated for provision of transport services. The article presents segmentation of stops and gives a definition of their tasks. The main part of the article describes stops problems and gives proposals to their solutions in location and identification, wheelchair accessible, technical condition, cleanness and amenities.
Keywords: wheelchair accessible; transport service; the owner of stops; passenger transport; stop indication; stop